Effect of Spacer Length on the Specificity of Counterion-Cationic Gemini Surfactant Interaction - Sood, Rohit; Alakoskela, Juha-Matti; Sood, Anjali; Vitovic, Pavol; Kinnunen, Paavo K.J. (Journal of Applied Solution Chemistry and Modeling, 2012)
Aqueous solutions of three dicationic quaternary N,N-dimethylammonium gemini surfactants with identical hydrocarbon tails (N-hexadecyl) separated by flexible two, four, and six carbon atom spacers (di-, tetra-, and hexamethylene), abbreviated as G2, G4, and G6, respectively, were characterized using dynamic light scattering (DLS), Langmuir balance, differential scanning calorimetry (DSC), and microscopy in the presence of varying concentrations of sodium salts of fluoride, chloride, bromide, and iodide. Clear dependence on the counterion species was evident in the surface activity of the geminis, as follows. In 0.1 mM salt minima in surface tension and hence presumably the highest affinity for G2, G4, and G6 were observed with fluoride/chloride, bromide, and iodide, respectively. This same ion specificity of G2, G4, and G6 was evident also in the changes of average hydrodynamic diameters (Zav) with temperature. More specifically, maximum in Zav for G2 was observed in 100 mM NaCl, for G4 in 100 mM NaBr, and for G6 in 1 mM NaI. Our results demonstrate that spacer length has a profound impact on the interaction of these surfactants with halide counter-ions of different sizes, controlling the organization of these cationic geminis in the presence of salt. Importantly, our studies show that adjusting the headgroup structure it is possible to design amphiphiles, which can be used to bind specific metal ions in solution, for purposes such as water purification and mineral enrichment.